2022
DOI: 10.1038/s41408-022-00748-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating complete remission with partial hematologic recovery (CRh) as a response criterion in myelodysplastic syndromes (MDS)

Abstract: Myelodysplastic syndromes (MDS) treated with DNMTI therapy have responses according to the 2006 IWG response criteria. CR responses have had the strongest association with OS. Recently, CR with partial hematologic recovery (CRh; i.e. blasts <5%, ANC > 500, platelets > 50) has been evaluated in AML, but its relevance is unknown in MDS. We identified adult patients with MDS treated with DNMTIs. We assessed best overall response to therapy according to IWG 2006 criteria, and subsequently identified patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 23 There is a need to develop and validate new response criteria for higher-risk MDS that capture meaningful clinical benefits, similar to the introduction of CR with partial hematological recovery in ELN 2022 AML criteria. 22 , 24 , 25 Conversely, the elimination of responses with doubtful clinical benefits (eg, marrow CR without meaningful count recovery) should be considered. 26 …”
Section: To Establish and Systematically Validate Clinically Meaningf...mentioning
confidence: 99%
“… 23 There is a need to develop and validate new response criteria for higher-risk MDS that capture meaningful clinical benefits, similar to the introduction of CR with partial hematological recovery in ELN 2022 AML criteria. 22 , 24 , 25 Conversely, the elimination of responses with doubtful clinical benefits (eg, marrow CR without meaningful count recovery) should be considered. 26 …”
Section: To Establish and Systematically Validate Clinically Meaningf...mentioning
confidence: 99%
“…61 Although CRh has not been shown in MDS to correlate with OS or other hard endpoints, a less stringent PB count recovery in the setting of CR may have meaningful implications for patients with MDS. In HR-MDS, Brunner et al 66 explored CRh as a potential endpoint in MDS and concluded that patients who reached CRh or an equivalent response following treatment had a comparable survival to those who achieved CR. Given the relevance of hematologic recovery in MDS, it is essential to evaluate CRh and CR L and their correlation with OS and therapeutic efficacy in prospective randomized studies.…”
Section: Marrow Complete Remissionmentioning
confidence: 99%
“…49,50 Other meaningful endpoints include the duration of a given response to therapy, as well as overall survival, although these are later endpoints for clinical study. 48 There are additional efforts underway to identify novel responses that are clinically meaningful and may serve as surrogates for overall survival, such as CRh (complete remission with incomplete hematologic recovery) or other combination endpoints, 51 but these remain exploratory at Are We Ready For "Triplet" Therapy in Higher-Risk MDS? this time.…”
Section: Outcomes/efficacy and Trial Regulatory "Success" With Triple...mentioning
confidence: 99%